2022
DOI: 10.1159/000528155
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Is a Safe and Effective Alternative to Radioisotope in Breast Cancer Sentinel Lymph Node Biopsy regardless of Patient Body Mass Index

Abstract: Introduction: A recent meta-analysis [1] has confirmed high sensitivity of indocyanine green (ICG) fluorescence mapping for sentinel node detection in early breast cancer. Concerns have previously been raised regarding the efficacy in patients with high body mass index (BMI). Materials and Methods: All consecutive patients undergoing sentinel lymph node biopsies (SLNB) for early breast cancer in NHS Tayside were included in a prospective audit of surgical and pathology findings. All patients included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Indocyanine green, a nonallergenic and nonradioactive fluorescent dye, has been proposed as an effective tracer for SLN identification in breast cancer. [10][11][12] It is well known that the SLN detection rates of ICG are superior to those of BD 15 ; however, the efficiency in SLN identification between ICG and RI method is controversial. Stoffels et al 16 found the use of ICG for SLN detection to be inferior compared with RI technique especially in patients in whom the lymph node basin cannot be predicted correctly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indocyanine green, a nonallergenic and nonradioactive fluorescent dye, has been proposed as an effective tracer for SLN identification in breast cancer. [10][11][12] It is well known that the SLN detection rates of ICG are superior to those of BD 15 ; however, the efficiency in SLN identification between ICG and RI method is controversial. Stoffels et al 16 found the use of ICG for SLN detection to be inferior compared with RI technique especially in patients in whom the lymph node basin cannot be predicted correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Indocyanine green, a nonallergenic and nonradioactive fluorescent dye, has been proposed as an effective tracer for SLN identification in breast cancer. 10-12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, blue dye and isotopic labeling are used for this. In recent years, the use of ICG for the detection of lymphatic vessels and lymph nodes has become widespread [3].…”
Section: ) Breast Surgerymentioning
confidence: 99%
“…Sentinel lymph node biopsy has been validated as a standard of care in breast cancer, melanoma and gynaecological malignancies [1][2][3]. With regards to endometrial and cervical cancer, the use of ICG uorescence imaging has been extensively investigated and has proven to be a safe, time-e cient and reliable method compared to standard tracers such as the Patent blue and technetium 99m [4].…”
Section: Introductionmentioning
confidence: 99%